Examining an Islamic Financial Inclusivity and Its Impact on Fundamental Economic Variables in Indonesia (An Approach of Static Panel Data Analysis) - Andre Pupung Darmawan; Angga Erlando; Dwi Budi Santoso (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT Previous studies mostly measured sharia financial inclusion using an index consisting of three dimensions: accessibility, availability, and usage. This research develops it by adding a digitalization dimension so that there are 4 dimensions in measuring sharia financial inclusion in Indonesia using an index. The first objective of this study is to visually illustrate the results of calculating the sharia financial inclusion index (in map form) in 33 provinces in Indonesia, using GeoDa software. Second, analyze the impact of sharia financial inclusion variables (the 4 form dimensions) that are calculated, on economic fundamental variables (growth, unemployment, poverty, and inequality) through a quantitative approach based on panel data analysis methods (FEM and REM). The secondary data used comes from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS), in the 2015-2020 period. The results of this study indicate that sharia financial inclusion in Indonesia needs to be increased more evenly, so that it is not stagnant and centered in Java or provinces with a communal Muslim base (viewed from the results of index calculations) because the values "‹"‹are unequal between provinces. Meanwhile, the results of panel data analysis techniques show that variables reflecting the 4 dimensions of sharia financial inclusion have an impact on fundamental economic variables. Keywords: Sharia Financial Inclusion, Index, GeoDa, Panel data   ABSTRAK Kajian sebelumnya banyak mengukur inklusi keuangan syariah dengan menggunakan indeks yang terdiri dari tiga dimensi: aksessibilitas, availabilitas, dan penggunaan. Penelitian ini mengembangkannya dengan menambah dimensi digitalisasi, sehingga terdapat 4 dimensi dalam mengukur inklusi keuangan syariah di Indonesia menggunakan indeks. Tujuan pertama penelitian ini menggambarkan visual hasil perhitungan indeks inklusi keuangan syariah (dalam bentuk peta) di 33 provinsi yang ada di Indonesia, dengan software GeoDa. Kedua, menganalisis pengaruh variabel inklusi keuangan syariah (4 dimensi pembentuknya) yang dihitung, terhadap variabel fundamental ekonomi (pertumbuhan, tingkat pengangguran, kemiskinan, dan ketimpangan) melalui pendekatan kuantitatif berbasis metode analisis data panel (FEM dan REM). Data yang digunakan bersumber dari Otoritas Jasa Keuangan (OJK) dan Badan Pusat Statistika (BPS), dalam periode 2015-2020. Hasil penelitian ini, menunjukkan bahwa bahwa inklusi keuangan syariah di Indonesia perlu ditingkatkan lebih merata, agar tidak stagnan terpusat di Java atau provinsi dengan basis muslim komunal, jika dilihat dari hasil perhitungan indeks yang nilainya timpang antar porvinsi. Sementara itu, hasil teknik analisis data panel menunjukkan bahwa variabel yang mencerminkan 4 dimensi inklusi keuangan syariah berdampak bagi variabel fundamental ekonomi. Kata Kunci: Inklusi Keuangan Sharia, Indeks, Geoda, Data Panel.